Management of The Santri Executive Board in Human Resource Development at The Hidayatullah Islamic Boarding School - Ida Nuryana; Akhmad Sirojuddin (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study aims to analyze the role of the Santri Hidayatullah Youth Movement (GPH) in developing the human resources (HR) of santri at the Hidayatullah As an intra-boarding school organization, GPH plays a strategic role in fostering leadership, responsibility, and social skills among santri. This study employs a qualitative approach using the case study method. Data was collected through participatory observation, in-depth interviews with eight key informants ( mentors, core committee members, and department coordinators), and analysis of documentation such as activity records and organizational structure. The research findings indicate that the implementation of management functions such as planning, organizing, executing, and evaluating programs contributes significantly to the development of students' competencies, particularly in leadership, teamwork, and independence. The effectiveness of these roles is highly dependent on the intensity of guidance provided by the pesantren and the continuity of the cadre system within the GPH structure. These findings indicate that strengthening santri organizational management is a crucial factor in supporting sustainable human resource development within the pesantren environment.